Pergeseran pola maqasid al-shari‘ah dari tradisional menuju modern: membaca pemikiran Jasser Auda - Ahmad Munjin Nasih (Ijtihad : Jurnal Wacana Hukum Islam dan Kemanusiaan, 2011)
In study of Islamic law there is an interesting topic to discuss, that is maqasid al-shari‘ah. Recently some Muslim scholars study further the applying of principle of daruriyat al-khamsah in a legal problem. Unfortunately Islamic jurists often apply the principle of daruriyat al-khamsah independently apart from other sciences besides usul al-fiqh. Difficulties and failure in deciding many contemporary legal problems rise to the result. Jasser Audah, a Muslim scholar from Egypt and lives in London proposes new idea to cope with this problem. According to Audah, at first we must separate maqasid al-shari‘ah from usul alfiqh in order to be independent knowledge. Then we combine it with modern sciences in studying legal problem. Only through this method, Auda believes that Islamic law will be more adaptable with the changing situation. In order to do his idea in developing maqasid al-shari‘ah, Auda specifically suggests five steps, that are: validating all cognitios, holism, openness and self-renewal, multi-dimensionality, and purposefulness.